VD_FINDINFO Jug / 2014 / 10 vom 21. Mai 2013 - VD Tribunal cantonal (2013)
LÉSION CORPORELLE PAR NÉGLIGENCE, PEINE PÉCUNIAIRE, DÉPENS | 125 al. 1 CP, 125 al. 2 CP, 34 CP, 42 al. 1 CP, 42 CP, 44 al. 1 CP, 44 CP, 47 CP